Lupine flour using in technology of restaurant industry establishment production - Hrebeniuk, I.; Bondar, Natalia; Yurchuk, Lyudmila (My University, 2013)
Using of food lupine in culinary product technology has been investigated.
Keywords: харчовий люпин; пищевой люпин; food lupine; білок; белок; protein; харчова цінність; пищевая ценность; nutritional value; хімічний склад; химический состав; chemical composition; ресторанний бізнес; ресторанный бизнес; restaurant business; кафедра іноземних мов професійного спрямування; кафедра готельно-ресторанної справи